Pengaruh Extra Virgin Olive Oil (EVOO) terhadap Berat Plasenta dan Berat Badan Janin pada Tikus Wistar Model Preeklampsia - Dwi Norma Retnaningrum; Wenny Rahmawati; Alfima Rahasti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Preeclampsia was defined as new onset hypertension and proteinuria after 20 weeks of gestation in which the mother had no previous history of hypertension. Preeclampsia is a disorder that often occurs in pregnancy with an incidence rate of 2-8% among pregnancies in the world. Preeclampsia ranks 2nd as a cause of maternal death (MMR). In East Java, preeclampsia was ranked 1st as the cause of AKI in 2016. Preeclampsia as one of the main causes of maternal death can be detected and treated properly before the emergence of life-threatening complications such as eclampsia. In severe cases, preeclampsia increases the risk of comorbidities such as Hemolysis, Elevated Liver Enzyme Levels, and Low Platelet Levels (HELLP) syndrome, edema, Disseminated Vascular Coagulation (DIC), and eclampsia/cerebral edema, whereas in fetus preeclampsia is associated with intrauterine growth restriction. (IUGR), prematurity and fetal death. Extra virgin olive oil (EVOO) is obtained from olives in a mechanical way that does not change the composition of the oil. Research on EVOO has been widely studied in a broad spectrum which explores its content as antioxidants and also anti-inflammatory polyphenols and tocopherols that can be used as anti-oxidants and also anti-inflammatory. The purpose of this study was to prove the role of EVOO on placental and fetal weight in preeclampsia model Wistar rats. The design of this study was experimental (quasi experimental) with a posttest only control group design approach. This study consisted of 5 groups, negative group, positive group (preeclampsia model rats), treatment groups 1, 2 and 3, namely preeclampsia rats that were given EVOO in 3 different doses (each 0.5ml/day, 1ml/day, 2 ml/day). After being sacrificed, the placenta and fetus are weighed to determine their weight. The results showed that the administration of EVOO was effective in increasing the weight of the placenta and fetus in preeclampsia model rats with a P value of 0.000 (P<0.05).